Tinnitus referral pathways within the National Health Service in England: a survey of their perceived effectiveness among audiology staff - Gander, Phillip E.; Hoare, Derek J.; Collins, Luke C.; Smith, Sandra; Hall, Deborah A. (BioMed Central, 2011)
Background: In the UK, audiology services deliver the majority of tinnitus patient care, but not all patients experience the same level of service. In 2009, the Department of Health released a Good Practice Guide to inform commissioners about key aspects of a quality tinnitus service in order to promote equity of tinnitus patient care in UK primary care, audiology, and in specialist multi-disciplinary centres. The purpose of the present research was to evaluate utilisation and opinions on pathways for the referral of tinnitus patients to and from English Audiology Departments. Methods: We surveyed all audiology staff engaged in providing tinnitus services across England. A 36-item questionnaire was mailed to 351 clinicians in all 163 National Health Service (NHS) Trusts identified as having a tinnitus service. 138 clinicians responded. The results presented here describe experiences and opinions of the current patient pathways to and from the audiology tinnitus service. Results: The most common referral pathway was from general practice to a hospital-based Ear, Nose & Throat department and from there to a hospital-based audiology department (64%). Respondents considered the NHS tinnitus referral process to be generally effective (67%), but expressed needs for improving GP referral and patients’ access to services. ‘Open access’ to the audiology clinic was rarely an option for patients (9%), nor was the opportunity to access specialist counselling provided by clinical psychology (35%). To decrease the number of inappropriate referrals, 40% of respondents called for greater awareness by referrers about the audiology tinnitus service. Conclusions: Respondents in the present survey were generally satisfied with the tinnitus referral system. However, they highlighted some potential targets for service improvement including 1] faster and more appropriate referral from GPs, to be achieved through education on tinnitus referral criteria, 2] improved access to psychological services through audiologist training, and 3] ongoing support from tinnitus support groups, national charities, or open access to the tinnitus clinic for existing patients.